An Investigation into Teachers Practices of Teaching Early Reading and Practical problems in Its Implementation - Minwuyelet Andualem Desta (Universitas Islam Negeri Sultan Aji Muhammad Idris Samarinda, 2020)
The purpose of this study was to investigate practices of teaching early reading, and challenges teachers face in its implementation at the Ethiopian primary schools. The study was carried out in 224 grade two government primary schools found in the Amhara National regional State, west Gojjam zone, Ethiopia, in 2019/2020 academic year. To attain this objective, a descriptive research design was employed. The participants of the study were 112 English language teachers enrolled in the primary schools at Dembecha woreda, Jiga woreda, Jabitehinan woreda, and Bure woreda in west Gojjam zone. Interview, questionnaire, and observation were used to gather data. The findings revealed that teachers failed to practice the teaching of early reading in line with the purposes and principles of teaching early reading. Teachers used traditional way of teaching approach in teaching reading. The study also showed that teachers are deficiently trained regarding phonological awareness, alphabetic principle, reading comprehension, oral fluency, vocabulary, and phonemic awareness. Besides, lack of teachers training, lack of materials, and unrelated educational qualification were major impediments of teachers while implementing teaching early reading. Finally, it was recommended that teachers be given trainings about methods of English language teaching in general, and teaching early reading in particular.